Systematic Literature Review on Social Epistemology of Science: Knowledge Production in Scientific Communities - Yanti Kristina Sinaga; M. Manugeren; Efendi Barus (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This paper presents a systematic literature review of research published between 2015 and 2025 on the social epistemology of science, focusing on how scientific knowledge is produced within communities. Moving beyond traditional individualistic epistemologies, the review highlights four dominant themes: epistemic trust and authority, collaborative and collective knowledge production, institutional norms shaping epistemic practices, and epistemic injustice affecting marginalized groups. Findings reveal that scientific knowledge depends heavily on social interactions, trust networks, and institutional frameworks that guide what counts as credible and valuable knowledge. The review also uncovers the significant influence of funding structures, publication pressures, and performance metrics in shaping scientific inquiry, often privileging dominant voices and methodologies. Epistemic injustice emerges as a critical issue, emphasizing the need for more inclusive and diverse epistemic practices within science. By synthesizing philosophical and empirical work, this study underscores the importance of understanding science as a socially situated and institutionally embedded practice. The paper concludes by advocating for greater integration of diverse perspectives and institutional reforms aimed at promoting epistemic equity, accountability, and transparency. This social epistemological approach offers a promising framework for rethinking scientific knowledge production in ways that are more democratic, ethical, and responsive to contemporary challenges.